(untitled) (Veterinary Science Development, 2017)
The senile female dog suffering from rheumatoid arthritis was clinically and clinicopathologically examined. The articular lesions localized in the elbows, stifles, and the carpal and tarsal joints. The dog with clinical signs of arthritis developed draining nodular lesions in the involved joints. The affected joints became swollen, and then serous exudates were observed in their ulcerative lesions. In addition, the dog developed leaks of milk (lactorrhea) in response to suckling stimuli. There were no abnormal values in hematological and blood coagulation profiles. Serum biochemical examinations showed an increase in total protein concentrations. Serum protein electrophoresis confirmed a prominent decrease in albumin and moderate increases in β1, β2 and γ-globurin. The serum prolactin concentration was apparently higher than that of normal dogs. This affected dog had raised rheumatoid factors and immune complexes. Both antinuclear antibodies and direct Coombs test were positive and serum complement titers and anti DNA antibodies were increased in this dog. In conclusion, the present results revealed that lactorrhea characterized by hyperprolactinemia and autoimmunological profiles was one of important clinical predictors associated with an increased risk of rheumatoid arthritis.